Thailand - Secondary Education for Employment (Vol. 2 of 2) : Background Papers - World Bank (Washington, DC, 2013)
The study aims at assisting the Government in undertaking an evaluation of the system of secondary education, and skills development, in order to plan the many complex decisions, and future international finance assistance in the sector. The objectives of the study are to determine general employment trends, including a sampling of employer views on skill development; to evaluate the cost effectiveness, and quality of present academic, and vocational secondary education; and, to develop alternative scenarios for expansion of secondary education. Chapter 1 provides an overview of the changing Thai economy, and documents the growing importance of education, and skills for global competitiveness. An overview of labor market trends, and human capital development demonstrates the under-education of Thailand's labor force, thus reinforcing the need for high-quality education, and training for demand-driven skills development. Chapter 2 presents the factors motivating change in the system of education, and, examines the market forces driving the need for reform, and, argues the needs of the private sector rival those of most developed countries. Chapters 3 and 4, discusses the principles, and implications of governance, and administration, while arguing that certain principles, including attention to market forces, should guide policy decision-making. Chapter 5 stresses on the quality of education outcomes, by setting performance standards, assessing student, teacher, and school performance, and, harnessing technology to support education, and learning development, while Chapter 6, examines the cost implications of the reform program. The background papers look beyond schooling, examining the actual recruitment of workers in this increasing global economy.